Dynamic of adaptability united latent quality indicator of Deschampsia antarctica population from Galindez island (Argentine lslands, maritime Antarctic) during three seasons - Miryuta, N.; Parnikoza, I.; Shvydun, P.; Myryuta, A.; Poronnik, O.; Kozeretska, I.; Kunakh, V. (Ukrainian Antarctic Journal, 2015)
Complex adaptability dynamics in the six populations of Deschampsia antarctica Desv. (Galindez lsland, Argentine Islands, maritime Antarctic) has been investigated during three south astral seasons. The adaptability united latent quality indicator has bееn shown to bе depended as from growing microcondition as from yearly weathering condition. The nature of adaptability united latent quality indicator dynamic trend allowed to group investigated populations bу form of trend to three groups: monotonic growth, or monotonic recession, or passage through maximum. Next row addition of united latent quality indicator of adaptability dynamics would allow to compare it with corresponding climatic indicator dynamics.